Housing retrofit: six types of local authority energy service models. Issue 1 (23rd June 2021) - Tingey, Margaret; Webb, Janette; van der Horst, Dan
Given the ambitious policy target to become net zero carbon by 2050, what role can local authorities play in the decarbonisation of housing? An examination is presented of six local authority energy service models relevant to housing retrofit in Britain. Local authorities have an important role, with local knowledge about housing stock and economic opportunities; they also have relevant planning and governance responsibilities. However, relatively little is known about either the different energy service models adopted for retrofit or their relative effectiveness. Models identified from empirical case study research constitute experimental innovations resulting from constrained finances and competition requirements in public services. They provided (1) energy-efficiency upgrades to public, residential and commercial buildings and/or (2) district heating infrastructure to secure 'upstream' resource efficiencies. Findings show that local initiatives provided different retrofit mixes, with differing potential for effective change. The limitations of current models are considered, along with the policy and market changes needed to empower local authorities to contribute systematically to net zero carbon buildings. Policy relevance: How can British local authorities organise energy-efficiency retrofit in buildings? Six energy service models are identified which deliver on-site energy-efficiency upgrades and/or area-based efficient heating infrastructure. Reductions to energy demand from these models tend to fall short of the radical changes required by UK net zero 2050 goals. Whilst the energy service models provide examples of local innovation and effectiveness, much more ambitious policy is essential to enable a step change in energy service models for retrofit. Policy and regulatory changes are needed: first, to reform the energy retail market to support energy services geared to reducing demand; and second, to empower local authorities and their partners to scale up whole-area retrofitting, including privately owned buildings.